Baim Wong Digital Footprint Formation of Online Identity in the Social Media Era : Jejak Digital Baim Wong Pembentukan Identitas Daring di Era Media Sosial - Lestari, Tri Yunanda Ayu (Procedia of Social Sciences and Humanities, 2025)
In the era of rapidly growing social media, public figures like Baim Wong face complex challenges in shaping and managing their online identities. This article analyzes in depth how Baim Wong, as an Indonesian celebrity, builds his online identity on various digital platforms, such as Instagram and YouTube, and how he manages the phenomenon of "context collapse" that often occurs in cyberspace. On the one hand, social media provides a great opportunity to connect directly with fans and introduce a more human and relatable self-image. However, on the other hand, it also poses great challenges in maintaining authenticity, privacy, and control over the information shared. Baim Wong, through various uploaded contents, not only displays a happy personal life with his family, but also uses social media for philanthropic activities and promotion of professional projects. However, with all the potential that exists, there are also privacy risks that must be faced, such as the potential for exploitation of personal data by third parties or threats to family security that often appear in his uploads. In building his online identity, Baim Wong prioritizes a balance between openness to the audience and protection of sensitive information, which is reflected in the way he chooses narratives that are acceptable to various audiences without sacrificing his personal privacy and security. Highlights: Building a Relatable Identity – Baim Wong strategically uses social media to connect with fans by sharing personal moments, philanthropic efforts, and professional projects. Managing Context Collapse – He navigates diverse audience expectations by carefully curating content that balances authenticity, privacy, and public perception. Privacy and Security Risks – Despite the benefits of social media, he faces challenges such as data exploitation and family security threats, requiring careful information management. Keywords: Online Identity, Social Media, Context Collapse, Authenticity, Digital Privacy